Watch the tone of your voice! An exploration of dehumanization of women by gender nonconformity based on tone of voice, occupation and appearance - Tanriverdi, Veysi; Yurdagül, Aydan; Tulum, Ezgi Aze; Ozbilgin, Mustafa F. (Frontiers in Psychology, 2024)
Dehumanization refers to the act of likening others to objects or animals. This, in turn, mitigates feelings of conscience, guilt, and moral obligation in the face of behaviors such as violence, mistreatment, or discrimination against the dehumanized individuals. The aim of this study is to determine the extent of which women with mismatching vocal tone, occupation and appearance to their gender expectations are dehumanized by others. To achieve this, we conducted a between-groups factorial design experiment. In the experiment, participants looked at the photo and listened to the voice of a target woman with either a gender congruent or incongruent vocal tone, occupation, or appearance. Participants indicated the extent to which human attributes were appropriate for this individual. The results revealed that the main effects of vocal tone and occupation were significant for both mechanistic and animalistic dehumanization. A target woman with a mismatched vocal tone and occupation was more dehumanized compared to those with a matched vocal tone and occupation. However, the interaction effect of vocal tone, occupation type, and appearance was found to be significant only for mechanistic dehumanization. Our study provides evidence to recent concerns that women may experience dehumanization due to their vocal tone and occupation.